(untitled) (Analysis in Theory and Applications, 2017)
In the present paper, we propose the q analogue of Szász-Beta-Stancu operators. By estimate the moments, we establish direct results in terms of the modulus of smoothness. Investigate the rate of point-wise convergence and weighted approximation properties of the q operators. Voronovskaja type theorem is also obtained. Our results generalize and supplement some convergence results of the q-Szász-Beta operators, thus they improve the existing results.